Back cover: Cardiovascular Benefits of Phenol‐Enriched Virgin Olive Oils: New Insights from the Virgin Olive Oil and HDL Functionality (VOHF) Study. Issue 16 (24th August 2018) - Pedret, Anna; Fernández‐Castillejo, Sara; Valls, Rosa‐Maria; Catalán, Úrsula; Rubió, Laura; Romeu, Marta; Macià, Alba; López de las Hazas, Maria Carmen; Farràs, Marta; Giralt, Montse; Mosele, Juana I.; Martín‐Peláez, Sandra; et al.
Abstract : Mol. Nutr. Food Res. 2018, 62, 1800456 DOI:10.1002/mnfr.201800456 HDL functionality is a better atheroprotection marker than serum HDL‐cholesterol. The "Virgin Olive Oil (VOO) and HDL Functionality" study assesses whether VOOs, enriched with their own phenolic compounds or with these plus complementary ones from thyme, enhance the functionality of HDL. Both VOOs promoted cardioprotective benefits improving HDL functionality and other cardiovascular risk factors according to phenol source and content. Further details can be found in article number1800456 by Sara Fernández‐Castillejo and co‐workers.